The relevance of feedback environment for job satisfaction - Mosquera, Pilar (2019)
The effectiveness of feedback given by managers in performance appraisal processes is largely influenced by situational factors and has important repercussions for employee performance and satisfaction. This study attempts to clarify the role played by two situational factors, Feedback Environment and Satisfaction with Feedback, for employee Job Satisfaction. Using a sample of 170 participants, the study analyses a conceptual framework and tests hypotheses through Partial Least Squares (PLS). Results indicate an impact of two dimensions of Feedback Environment, namely Source Credibility and Feedback Quality, for both Satisfaction with Feedback and Job Satisfaction. It was also found that age is a moderator of the relationship between the two Feedback Environment dimensions and Satisfaction with Feedback: the older the employees, the lower the effect of Feedback Quality and the higher the effect of Source Credibility for Satisfaction with Feedback. Contrary to expectations, Satisfaction with Feedback does not mediate the relationship between Feedback Environment and Job Satisfaction.